Elevating Students’ Narrative Writing Ability Through Local Legend Picture Series - Syailendra, Axel; Karim, Sayit Abdul; Matas, Gordan; Ramli, Ramli; Ismail, Hijril (Journal of Languages and Language Teaching, 2024)
This research aimed to detect students' ability to write narrative text using local legendary picture series and further explore their perceptions of using picture series in writing narratives. A descriptive quantitative research design was employed, and 30 students (10 males and 20 females) participated as respondents in the present study. Furthermore, the students were asked to write a narrative text based on a series of pictures from the local legend of Danau Toba. The findings indicated that picture series significantly enhanced students' narrative writing skills. The average scores revealed that the organization, vocabulary, and grammar were 3.19, 3.43, and 2.92 respectively, categorized into the "Good" level. Meanwhile, the average score for mechanical ability was 2.46, categorized as "Enough". Furthermore, the majority of students viewed positively to the use of picture series, with 46.67% strongly agreeing and 46.67% agreeing that picture series enhanced their ability to absorb and retain information. Thus, the picture series used are effective media for learning narrative writing skills. This study may serve pedagogical implication to the teaching of writing skills. Therefore, the researchers recommend that teachers integrate picture series in their teaching strategies and next researchers could explore the use of picture series in other text types and across various English language skills to provide broader insights and potentially more robust pedagogical strategies.